2009
DOI: 10.1007/s10734-009-9293-y
|View full text |Cite
|
Sign up to set email alerts
|

Employee wellbeing in the higher education workplace: a role for emotion scholarship

Abstract: This article has dual aims. First, it proposes an explicit focus on emotion as a means of enriching thinking about employee health and wellbeing in the higher education (HE) sector. Second, in order to bring conceptual clarity to a highly complex area, it presents and illustrates (using a fictional scenario) a framework for understanding emotion. The article begins with an overview of recent published research relevant to the HE workplace as an affective domain and argues that research with an explicit focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…Vandervoort (2006) explains that considering the potential effectiveness of emotional intelligence being included in the secondary school curriculum, (for example : Caplan, et al, 1992;Cohen, 1999) similar results could be expected at the college level. Woods (2010) argues that whereas research has been carried out at school level, little research has been undertaken with academics in higher education. There is, therefore, a clear argument for research to be carried out in this area and to evaluate the concept of emotional intelligence in the higher education context (University) and to investigate the relationship between emotional intelligence and well-being.…”
mentioning
confidence: 99%
“…Vandervoort (2006) explains that considering the potential effectiveness of emotional intelligence being included in the secondary school curriculum, (for example : Caplan, et al, 1992;Cohen, 1999) similar results could be expected at the college level. Woods (2010) argues that whereas research has been carried out at school level, little research has been undertaken with academics in higher education. There is, therefore, a clear argument for research to be carried out in this area and to evaluate the concept of emotional intelligence in the higher education context (University) and to investigate the relationship between emotional intelligence and well-being.…”
mentioning
confidence: 99%
“…Despite an expanding area of scholarship that addresses emotional labour in Higher Education (HE) (Constanti & Gibbs, 2004;Hagenauer & Volet, 2014;Postareff & LindblomYlänne, 2011;Woods, 2010), there is little that reflects on specific contexts and how procedural aspects of teaching might inherently involve emotional risks for both students and staff. This Practice Report looks at the administrative task of managing assignment extension requests as a call for more research into the ways that academics are engaged in the cycle of student and staff wellbeing in their teaching practices.…”
Section: Emotional Labour and Higher Educationmentioning
confidence: 99%
“…Diener and Diswas-Diener's (2008) research has found that satisfaction with relationships is the most important predictor for life-satisfaction. Developing competence in a range of cultural appropriate display rules can, thus, be regarded as an important factor for maintaining teachers' wellbeing (Woods, 2010) in international education settings at home or abroad (for a critical discussion on the increased emphasis on emotions and emotional well-being in education, see for example Ecclestone & Hayes, 2009;Ecclestone, 2012).…”
Section: Conclusion: Study Limitations and Implicationsmentioning
confidence: 99%